Otitis Media Caused by V. cholerae O100: A Case Report and Review of the Literature - Kechker, Peter; Senderovich, Yigal; Ken-Dror, Shifra; Laviad-Shitrit, Sivan; Arakawa, Eiji; Halpern, Malka (Frontiers in Microbiology, 2017)
Abstract Infections due to Vibrio cholerae are rarely documented in Israel. Here we report a case of recurrent otitis media in a young male, caused by V. cholerae non-O1/O139. This extra-intestinal infection was caused by V. cholerae O100 and has been associated with freshwater exposure and travel. Symptoms of chronic periodic earaches along with purulent exudate began about one week after the patient suffered a water skiing accident on a river in Australia. The condition lasted for three years, until his ear exudate was examined in a clinical laboratory, diagnosed and treated. Five bacterial isolates were identified as V. cholerae O100. The isolates were screened for genetic characteristics and were found positive for the presence of hapA, hlyA and ompU virulence genes. All isolates were negative for the presence of ctxA. Based on antibiogram susceptibility testing, ciprofloxacin ear drops were used until the patient’s symptoms disappeared. This case demonstrates that exposure to freshwater can cause otitis media by V. cholerae non-O1/O139 in young and otherwise healthy humans.